Empagliflozin improves pressure-overload-induced cardiac hypertrophy by inhibiting the canonical Wnt/β-catenin signaling pathway - Yuan, Xun; Pan, Li; Zhang, Chi; Zhu, Qiulian; Huang, Zexin; Qin, Yuan; Zhang, Guiping; Feng, Zhimei; Yang, Caixian; Hou, Ning (Frontiers in Pharmacology, 2024)
Background: Empagliflozin (EMPA) is an SGLT-2 inhibitor that can control hyperglycemia. Clinical trials have indicated its cardio-protective effects against cardiac remodeling in diabetes or non-diabetes patients. However, the underlying molecular mechanisms of EMPA’s cardio-protective effects remain elusive. Methods: We evaluated whether the EMPA attenuated the pressure-overload-induced cardiac hypertrophy by inhibiting the Wnt/-catenin pathway. Furthermore, the effects of the EMPA on a mouse model of transverse aortic constriction (TAC) induced cardiac hypertrophy was also evaluated. Mice were administrated with 0.5% CMC-Na as a vehicle or EMPA (10 mg/kg/day, daily, throughout the study) by intragastric gavage. Results: The in vivo echocardiography and histologic morphological analyses revealed that EMPA attenuated TAC-induced cardiac hypertrophy. Moreover, it also ameliorated TAC-induced cardiac fibrosis and decreased the cell size of the cardiomyocytes in isolated adult cardiomyocytes. Molecular mechanism analysis revealed that the EMPA reduced the TAC-induced enhanced expression of the Wnt/-catenin pathway in vivo. For in vitro assessments, isolated neonatal rat cardiomyocytes (NRCMs) were treated with Angiotensin II (AngII) and EMPA; the results showed that in the absence of EMPA, the expression of the Wnt/-catenin pathway was enhanced. In the trans-genetic heterozygous β-catenin deletion mice, EMPA attenuated TAC-induced cardiac remodeling by reducing the Wnt/β-catenin pathway. In addition, molecular docking analysis indicated that EMPA interacts with FZD4 to inhibit the TAC and AngII induced Wnt/β-catenin pathway in cardiomyocytes. Conclusion: Our study illustrated that EMPA might directly interact with FZD4 to inhibit the TAC and AngII-induced activation of the Wnt/β-catenin pathway to attenuate the adverse cardiac remodeling.